Research trends in clean, green and sustainable manufacturing: a bibliometric review. Issue 10 (2022) - Caterino, M.; Rinaldi, M.; Fera, M.; Macchiaroli, R.; Bottani, E.
Abstract: This paper aims at conducing a bibliometric literature review targeting some key themes of sustainability in the manufacturing and production sector. A first sample of 631 papers was found by using an appropriate combination of keywords in the SCOPUS database over a 22 year period (2000-2021). The sample was then reduced to 563 manuscripts, by removing the papers not expressively focused on the targeted topic. Finally, the analysis of the author keywords was carried out by dividing the 22 years period into 4 timespans, to determine the past and current trends within the research topic. The results highlighted a dominance of general themes related to sustainable and green aspects; at the same time, some specific subjects related to different aspects of manufacturing and production were identified, such as the design, the performance evaluation and the introduction of new Industry 4.0 technologies. Other themes, like human factors, companies' resilience, flexibility or agility, appear to be not so considered in the studies reviewed; these themes could represent interesting topics for future research activities.